Effect of Ultraviolet C Disinfection Treatment on the Nanomechanical and Topographic Properties of N95 Respirator Filtration Microfibers. (2020) - Meng, Yujie; Zeng, Rae; Rubin, Kurt; Barry, Kelly
Abstract: Ultraviolet germicidal irradiation (UVGI) N95 filtering facepiece respirator (FFR) treatment is considered an effective decontamination approach to address the supply shortage of N95 FFRs during the ongoing Covid-19 pandemic. In this study, we investigated the nanomechanical and topographic properties of filtration fibers that have been exposed to different doses of UVC radiation. UVC exposure was shown to decrease both Young's modulus (E), hardness (H) and fiber width, as measured on individual polypropylene (PP) fibers. Our results also show that the PP microfiber layer loses its strength when N95 respirators are exposed to an accumulated UVC dose during the process of decontamination, and the PP fiber width also exhibits a logarithmic decrease during UVC exposure. The nanoscale measurement results on individual fibers suggest that maximum cycles of UVC disinfection treatment should be limited due to excessive accumulated dose, which has the potential to decrease the fiber breaking strength.